Krieg und Kunst - Crispin, Julia (2018)
The English occupiers of France in the late phase of the Hundred Years War based their claims to the French crown not only on military conquest but also took great pains to depict it visually. The study examines the media for the visual depiction of political ideas and shows the major motivations and traditions in this effort and their intended audience.